2018
DOI: 10.1590/0001-3765201820170852
|View full text |Cite
|
Sign up to set email alerts
|

Volume equations for Khaya ivorensis A. Chev. plantations in Brazil

Abstract: African mahogany (Khaya spp.) plantations are in expansion in Brazil and in the world. This fact justifies the need for studies related to its growth and yield. This paper aimed to evaluate the performance of single-entry and double-entry models for estimating merchantable and total volume for Khaya ivorensis plantations before the first thinning (7 years) and expected final cut (15 years). Volume data was from 100 and 46 trees in Minas Gerais and Pará states, respectively, by using an electronic dendrometer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…The median estimated volume was 0.39 m 3 with mean ± SD of 0.76 ± 1.00 m 3 . Due to comparable soil types, that is, Humic Gleysol and ferric Luvisols, and similar humid equatorial climatic conditions for K. ivorensis growth, another specific function selected for this study was based on the prediction model developed in Minas Gerais state, Brazil 24 . Two classes were separated for this study estimation: first thinning (Dbh <30 cm) and final cut (Dbh ≥ 30 cm).…”
Section: Spatial Autocorrelation and Hot Spot Analysis The Results Omentioning
confidence: 99%
See 2 more Smart Citations
“…The median estimated volume was 0.39 m 3 with mean ± SD of 0.76 ± 1.00 m 3 . Due to comparable soil types, that is, Humic Gleysol and ferric Luvisols, and similar humid equatorial climatic conditions for K. ivorensis growth, another specific function selected for this study was based on the prediction model developed in Minas Gerais state, Brazil 24 . Two classes were separated for this study estimation: first thinning (Dbh <30 cm) and final cut (Dbh ≥ 30 cm).…”
Section: Spatial Autocorrelation and Hot Spot Analysis The Results Omentioning
confidence: 99%
“…Volume functions can be categorised into three classes: first, using Dbh as a sole predictor (local volume functions); second, having Dbh and Ht measurements as predictors (regional volume functions); and third, including Dbh, Ht, and an upper stem diameter as a surrogate for stem form, which is particularly good at the national scale (large-scale volume functions) 41 . Oliveira et al 24 suggested that double-entry models (Dbh and Ht predictors) are more accurate than single-entry models (Dbh predictor) when predicting K. ivorensis stand volume. This study adopted two approaches for indirect volume functions: the allometric volume equation (Eq.…”
Section: K Ivorensis Economic Valuementioning
confidence: 99%
See 1 more Smart Citation
“…We evaluate that most of the research that was published citing K. ivorensis from Brazilian plantations prior to 2019 were related to K. grandifoliola. The following works we are certain that studied K. grandifoliola, and not K. ivorensis as reported: Ribeiro et al (2016;2017;2018a;2018b); Mayrinck et al (2018); Oliveira et al (2018). While we are fairly sure -given the location mentioned on the Materials -of other research papers that report findings of K. grandifoliola and not K. ivorensis (e.g.…”
mentioning
confidence: 82%
“…The dendrometric characteristics observed in the present study corroborate those reported by Castro et al (2008) for silvipastural systems in which African mahogany can reach 12 m trunk height, with 22 cm DBH, at seven year of age. In a K. ivorensis pure stand, at seven years of age, the Ht and Hc averages were 17.1 and 7.7 m, respectively and DBH was 25.1 cm, in Piumhi, MG, Brazil (Oliveira et al, 2018).…”
Section: Vulnerabilidade De Mogno-africano à Predação Por Bovinos Em mentioning
confidence: 94%